INTEGRATION BETWEEN INSECT GROWTH INHIBITORS, TRIGARD AND Coccinella septempunctata (L.) IN CONTROLLING - Nazar M. Al-Mallah (Mesopotamia Journal of Agriculture)
Results of the integration study between insect growth inhibitors Trigard (Cyromazine 75% W.P.) and ladybird beetle Coccinella septempunctata (L.) in controlling black bean aphid, Aphis fabae (Scopoli), showed that Trigard exhibit a good effect in controlling Aphis fabae. The results also revealed the existence of variation in a predation efficiency of males and females of ladybird according to the treatment method and Trigard concentration, and showed that the highest average of males predation efficiency reached 56.8, and 53.5%, and for females 53.5, and 52.7% when the plant leaf treated by 0.15% Trigard concentration respectively. The results also showed a variation in average mortality percentage of Coccinella septempunctata (L.) males and females after five days from the treatment according to the treatment method and Trigard concentration, the highest mortality percentage in males and females were 47.3, and 43.2%, respectively when spraying Tigard at 0.5% concentration on plant leaf, Aphids and Ladybird together.